A taxonomic revision of the subfamily Myzininae from China, with a key to the Chinese species (Hymenoptera: Tiphiidae) - Liao, Xiang-Ping; Chen, Bin; Li, Ting-Jing (Zootaxa, 2022)
In this study, a total of 11 species belonging to four genera of Myzininae are recorded from China, among which a new species, namely Hylomesa punctata sp. nov. is described from Tibet and Yunnan, and four species are newly recorded. All the species are illustrated and a key to them is provided in this paper.